2020
DOI: 10.3390/catal10101180
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Facile Fabrication of Anion-Vacancy-Induced MoO3−X Catalysts for Enhanced Hydrogen Evolution Activity

Abstract: Advanced catalysts for clean hydrogen generation and storage offer an attractive possibility for developing a sustainable and ecofriendly future energy system. Transition metal oxides (TMO) are appealing candidates to be largely considered as electrode catalysts. However, for practical applications, there are still challenges—the intrinsic catalytic properties of TMOs should be further improved and TMOs should be synthesized by practical routes for cost-effective and scalable production of catalysts. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…[16][17][18] Among the metal oxide (MO) species, the transition metal oxides (TMOs) are being studied due to their abundance, low-cost, eco-friendly nature, and ease of fabrication. 19,20 Different TMO species like TiO 2 , MnO 2 , V 2 O 5 , Cr 2 O 3 , WO 3 , and Co 3 O 4 have been synthesized and tested for the HER and EC capacitors. [21][22][23][24][25][26] These TMOs are either doped with suitable transition metal (TM) atoms or an interfacial heterostructure is created with other metal oxides or carbon species to modify their band structures and make them viable for an improvement in their HER activity and stability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[16][17][18] Among the metal oxide (MO) species, the transition metal oxides (TMOs) are being studied due to their abundance, low-cost, eco-friendly nature, and ease of fabrication. 19,20 Different TMO species like TiO 2 , MnO 2 , V 2 O 5 , Cr 2 O 3 , WO 3 , and Co 3 O 4 have been synthesized and tested for the HER and EC capacitors. [21][22][23][24][25][26] These TMOs are either doped with suitable transition metal (TM) atoms or an interfacial heterostructure is created with other metal oxides or carbon species to modify their band structures and make them viable for an improvement in their HER activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…The anion-deficient MoO 3 (MoO 3Àx ) or low oxidation-stabilized MoO 2 (MoO 3Àx , x = 1) species that maintain the structural stability and layered characteristics are highly suitable for enhancing the electrocatalytic activities. 20,29,30 (1)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in recent years, transition metal oxides/sulfides have emerged as effective alternatives to Pt and Pt-based electrocatalysts. Numerous studies have been devoted to enhancing the electrochemical properties of transition metal oxides/sulfides/phosphides/ carbides [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. For example, Shen and Yin's research groups reported that the bimetallic nickel-cobalt phosphide shows improved HER activity and stability, due to its unique morphology with nanosheets on the 3D integrated framework, providing a large surface area and many active sites for HER [24].…”
Section: Introductionmentioning
confidence: 99%